Reminiscences: AINA - 1979-86, a Time of Transition - Schledermann, Peter (ARCTIC, 1987)
Since its inception the Arctic Institute has experienced many difficult episodes, not the least of which was the upheaval caused by the move from Montreal to Calgary. In 1979 AINA became an institute of the University of Calgary and embarked upon yet another time of transition.Key words: Arctic Institute of North America Dès ses débuts, l'Institut arctique a connu bien des périodes difficiles. L'une d'entre elles, et non la moindre, a été le bouleversement dû au déménagement de l'Institut de Montréal à Calgary. En 1979, l'Institut arctique de l'Amérique du Nord est devenu un institut de l'Université de Calgary, et est entré dans une nouvelle époque de transition.Mots clés: Institut arctique de l'Amérique du Nord